Antioxidant and hepatoprotective potentials of active fractions of Lannea barteri Oliv. (Anarcadiaceae) in rats - Mbaoji, Florence N. (Heliyon, 2020)
INTRODUCTION: Lannea barteri is used in the folkloric treatment of many disease states ranging from epilepsy, diarrhoea, oedema and ulcers, etc. This study investigated the antioxidant and hepatoprotective potentials of methanol (MFLB), n-hexane (nHFLB) and ethyl acetate (EFLB) leaf fractions of L. barteri and identified the active metabolites. MATERIALS AND METHODS: The in vitro models used were 1, 1-diphenyl-1-picrylhydrazyl (DPPH), reducing power and thiobarbituric acid assays while in the in vivo model, carbon tetrachloride-induced oxidative liver damage in albino rats was used, and the biomarkers assayed were aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), malondialdehyde (MDA), serum total protein, serum direct and total bilirubin. Also, histopathological examination of the liver, high performance liquid chromatography (HPLC) profiling and liquid chromatography-mass spectroscopy-electrospray ionization (LC-MS-ESI) analysis of the fractions were done. RESULTS: In the in vitro assays, the decreasing order of DPPH free radical scavenging activity of the ascorbic acid and fractions at 400 μg/ml is as follows: ascorbic acid (86.6%), MFLB (52.8%), EFLB (36.6%), and nHFLB (28.1%). The percentage scavenging activity of the samples at 400 μg/ml in the TBA followed this pattern: ascorbic acid (117.1%), MFLB (82.2%), nHFLB (80.0%), and EFLB (46.9%). The ascorbic acid elicited highest reducing power (42.6%), followed by MFLB (22.5%), nHFLB (13.7%), and EFLB (-0.93%). The in vivo study showed significant (p < 0.0001) reduction in serum AST, ALT, and direct bilirubin with a non-significant reduction in ALP, total bilirubin and MDA, and mild elevation in total protein. Histopathological studies revealed a restorative effect on liver architecture. The phytochemical analyses revealed the presence of resins, terpenoids, flavonoids, carbohydrates, alkaloids, reducing sugar, saponins, tannins and proteins. HPLC-ESI-MS analysis revealed the presence of potentially bioactive compounds in L. barteri fractions. CONCLUSION: The fractions from L. barteri leaf possessed in vitro antioxidant and hepatoprotective potentials against CCl(4)-hepatic oxidative damage; therefore, proper isolation and characterization of these identified bioactive compounds responsible for the observed effects are ongoing.